2010
DOI: 10.1111/j.1365-2036.2010.04252.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactose intolerance in patients with chronic functional diarrhoea: the role of small intestinal bacterial overgrowth

Abstract: SUMMARY BackgroundMany studies report a high prevalence of lactose intolerance in patients with functional, gastrointestinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 55 publications
(97 reference statements)
2
48
1
1
Order By: Relevance
“…We cannot set an answer whether the problem was only bacterial infection from the start or initiated a state of lactose intolerance that triggered the dermatitis. Zhao et al [36] concluded that small intestinal bacterial overgrowth increases the likelihood of lactose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot set an answer whether the problem was only bacterial infection from the start or initiated a state of lactose intolerance that triggered the dermatitis. Zhao et al [36] concluded that small intestinal bacterial overgrowth increases the likelihood of lactose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…SIBO increases the probability of lactose intolerance in patients with chronic functional diarrhea (CFD) as a direct result of lactose fermentation in the small intestine, irrespective of orocecal transit time and intestinal sensitivity [58].…”
Section: Association Between Sibo and Other Nosological Entitiesmentioning
confidence: 99%
“…Une telle intolérance est souvent secondaire à un apport excessif. Elle pourrait être également due à des anomalies qualitatives ou surtout quantitatives de la flore qui modifient le métabolisme endoluminal de ces sucres [10].…”
Section: Intolérance à Certains Sucres Et Aux Polyolsunclassified